GEOPOLYMER CEMENT FOR OIL WELL WITH IMPROVED PROPERTIES - Wan Ahmad Fahmi Azrin Che Mohd, Wan Ahmad Fahmi Azrin (Universiti Teknologi Petronas, 2011)
With the increasing awareness of global warming, geopolymer cement has been identified as one of the methods in reducing the emission of CO2 during oil well cementing operation. However, it is important that geopolymer cement can meet the specific requirement of oil well condition in order to be the substitute of current conventional cement system. The use of geopolymer in cement system is a new technology that yet needs proper study to yield better advantages of it. In this research, the main objective was to observe properties are thickening time, fluid loss and compressive strength. In the early stage, literature review on previous research showed utilizing geopolymer in cement composition will significantly reduce C02 emission and enhanced properties characteristic as well. Detailed study on geopolymer materials, conventional cement, and additives was carried out. As the conclusion, from the obtained results geopolymer cement showed better properties compared to conventional cement.